Sexual Health Knowledge of Teachers - Sinan Erten; Irem Akcam-Yalcin (Seyit Ahmet Kıray, 2019)
The aim of this study is to investigate the knowledge level of teachers regarding sexual health. The sample of the study consists of 462 teachers working at primary, middle and high schools in Turkey. As the study aims to determine the current status of teachers regarding sexual health knowledge, the relational screening model was used. The Cronbach's Alpha correlation coefficient was calculated and determined to be 0.782. t test and ANOVA were used for data analysis. The "Sexual Health Knowledge Scale" used within the scope of the sexual health course is a 5-point Likert scale and the possible score from the scale varies from 1 to 5. It is possible to say that the teachers had a high knowledge level regarding sexual health. Analysis showed that female teachers had a significantly higher knowledge level compared to male teachers, married teachers had a significantly higher knowledge level compared to single teachers, teachers who took the Sexual Health course during their undergraduate studies had a significantly higher knowledge level compared to teachers who did not, and teachers who received education regarding sexual health had a significantly higher knowledge level compared to teachers who did not.